2013
DOI: 10.1002/adsc.201200996
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde‐Catalyzed Transition Metal‐Free Dehydrative βAlkylation of Methyl Carbinols with Alcohols

Abstract: Different to the borrowing hydrogen strategy in which alcohols were activated by transition metal-catalyzed anaerobic dehydrogenation, the direct addition of aldehydes was found to be an effective but simpler way of alcohol activation that can lead to efficient and green aldehyde-catalyzed transition metal-free dehydrative C-alkylation of methyl carbinols with alcohols. Mechanistic studies revealed that the reaction proceeds via in situ formation of ketones by Oppenauer oxidation of the methyl carbinols by ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 56 publications
1
41
0
1
Order By: Relevance
“…Next, Xu and co‐workers found that when the β‐alkylation of 1‐phenylethanol (1 equiv) with benzyl alcohol (1.3 equiv) was carried out in the presence of 20 mol % benzaldehyde and 30 mol % KOH at 110 °C for 32 h under nitrogen, only 1,3‐diphenylpropanol was obtained in almost quantitative yield . The reaction pathway is similar to that reported in Scheme , with benzaldehyde fulfilling the same role played by O 2 (air) in the initial stage of the reaction allowing the Oppenauer mechanism to start.…”
Section: Tm‐free Dehydrative C−c Forming Reactions With Alcoholsmentioning
confidence: 53%
See 1 more Smart Citation
“…Next, Xu and co‐workers found that when the β‐alkylation of 1‐phenylethanol (1 equiv) with benzyl alcohol (1.3 equiv) was carried out in the presence of 20 mol % benzaldehyde and 30 mol % KOH at 110 °C for 32 h under nitrogen, only 1,3‐diphenylpropanol was obtained in almost quantitative yield . The reaction pathway is similar to that reported in Scheme , with benzaldehyde fulfilling the same role played by O 2 (air) in the initial stage of the reaction allowing the Oppenauer mechanism to start.…”
Section: Tm‐free Dehydrative C−c Forming Reactions With Alcoholsmentioning
confidence: 53%
“… β‐Alkylation of secondary alcohols with primary alcohols and the related aldehyde in the presence of KOH …”
Section: Tm‐free Dehydrative C−c Forming Reactions With Alcoholsmentioning
confidence: 99%
“…However, the result was not satisfactory with heteroatom containing arylacetonitriles even after longer period of heating. Hence, inspired by the Xu group's report of aldehyde promoted β‐alkylation of secondary alcohols with primary alcohols, the same reactions were carried out in presence of 20 mol % benzaldehyde which afforded the corresponding α‐alkylated nitriles in moderate yield ( 4 i – k ) …”
Section: Resultsmentioning
confidence: 99%
“…[115] With an aldehyde as the catalyst dehydrative C-alkylation of methyl carbinols with alcohols was realized. [116] By applying the concept of the redox chain reaction, indoles and pyrroles were alkylated with unactivated secondary alcohols [Eq. (40) and Scheme 19].…”
Section: Transition-metal-free Reactionsmentioning
confidence: 99%